1993
DOI: 10.1007/bf02048362
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of surgical resection for Crohn's disease

Abstract: One hundred fifty-two of 399 Crohn's patients (38 percent) diagnosed over 20 years, who lived within a geographically defined area at the time of diagnosis, underwent at least one operation. One hundred seventy-one resections were performed in 160 operations during a mean follow-up of 60 months. Forty-eight percent of patients had undergone their first resection within 10 years of diagnosis, and 39 percent of these had undergone a second resection within 10 years of the first. There was no difference between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 3 publications
0
15
0
Order By: Relevance
“…It is lowest when the repeat resection rate is considered, intermediate when clinical indices are used, and highest when endoscopy is used as a diagnostic tool. [1][2][3][4][5][6][7][8][9][10] Data from endoscopic follow up of patients after resection of ileocaecal disease have shown that in the absence of treatment, the POR rate is around 65%-90% within 12 months and 80%-100% within three years of the operation. The clinical recurrence without therapy is about 20%-25% per year.…”
Section: Epidemiology Of Postoperative CDmentioning
confidence: 99%
“…It is lowest when the repeat resection rate is considered, intermediate when clinical indices are used, and highest when endoscopy is used as a diagnostic tool. [1][2][3][4][5][6][7][8][9][10] Data from endoscopic follow up of patients after resection of ileocaecal disease have shown that in the absence of treatment, the POR rate is around 65%-90% within 12 months and 80%-100% within three years of the operation. The clinical recurrence without therapy is about 20%-25% per year.…”
Section: Epidemiology Of Postoperative CDmentioning
confidence: 99%
“…The occurrence of new mucosal (endoscopic) lesions in the neoterminal ileum early after surgery is almost constant, and it is followed in the mid-term by clinical symptoms and, in a proportion of patients repeated intestinal resections are required. As recently reviewed, clinical POR rates, assessed by conventional clinical activity indexes, varies between 17%-55% at 5 years, 32%-76% at 10 years and 72%-73% at 20 years [6] , whereas surgical POR rates (patients requiring re-operation) are of 11%-32% at 5 years, 20%-44% at 10 years and 46%-55% at 20 years [6][7][8] .…”
Section: Definition Of Postoperative Recurrencementioning
confidence: 99%
“…1 2 However, it is apparent that approximately 80% of patients presenting with ileal disease will require surgical intervention at some stage in their lifetime. [3][4][5] Realisation that the extent of disease resection and the extent of lymph node clearance does not affect disease recurrence rates, 6 7 and the increasing use of strictureplasty in obstruction, 8 has improved surgical strategies in Crohn's disease without compromising small bowel mucosal area. However, Crohn's disease cannot be cured by surgical intervention and thus the principles of management should include the relief of symptoms, minimising the risks of therapy and disease recurrence.…”
Section: A C J Windsormentioning
confidence: 99%